2021
DOI: 10.1186/s12886-021-02085-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the information needs of contact lens wearers for better education and more support: a qualitative study

Abstract: Background Designing educational interventions tailored to the needs of Contact Lens Wearers (CLWs) are important and necessary. The present study aimed to determine the information needs of CLWs to educate and provide information to them to increase their knowledge and reduce complications and non-compliance behaviors. Methods A qualitative approach was applied and semi-structured interviews were conducted in three contact lenses (CL) clinics in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Our study findings showed that the CL wearers need to have knowledge regarding different aspects of the CL such as CL use and care, CL training regarding application and removal, rinsing and disinfecting of CLs, brands and certified sale center to perform CL care, and information to prevent complications, and preferred to develop the mobile application content based on the reported information needs. In agreement with our findings, various studies have determined that CL wearers have different information needs [ 16 ] and limited knowledge related to using and caring for CLs, potential complications of CLs, cleaning of CLs and cases, and hand hygiene [ 10 , 15 , 24 , 25 ]. In line with our findings, several studies suggested the need for the development of training strategies and also providing enough information and theoretical and practical education for CL wearers to be knowledgeable about all aspects of the CL use and care [ 1 , 2 , 10 , 14 , 18 , 25 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study findings showed that the CL wearers need to have knowledge regarding different aspects of the CL such as CL use and care, CL training regarding application and removal, rinsing and disinfecting of CLs, brands and certified sale center to perform CL care, and information to prevent complications, and preferred to develop the mobile application content based on the reported information needs. In agreement with our findings, various studies have determined that CL wearers have different information needs [ 16 ] and limited knowledge related to using and caring for CLs, potential complications of CLs, cleaning of CLs and cases, and hand hygiene [ 10 , 15 , 24 , 25 ]. In line with our findings, several studies suggested the need for the development of training strategies and also providing enough information and theoretical and practical education for CL wearers to be knowledgeable about all aspects of the CL use and care [ 1 , 2 , 10 , 14 , 18 , 25 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the high workload of practitioners may hinder them from consistently providing adequate CL care and compliance information [ 8 , 12 , 13 ]. This is highlighted by some previous studies that have shown that CL wearers have little knowledge related to CL care and compliance [ 1 , 4 , 5 , 14 , 15 ] and have various information needs in this field [ 16 ]. These researchers furthermore emphasized the need to move away from conventional teaching practices and toward new educational strategies that involve modern technology [ 5 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of CLs for fashion purpose among young people in this review is high, there is a tendency for increased ocular complications in this age group due to poor compliance [9]. There is need for targeted CL education either in form of booklet or media campaign to encourage proper lens hygiene and improve compliance [27].…”
Section: Discussionmentioning
confidence: 95%
“…While the use of CLs for fashion purpose among young people in this review is high, there is a tendency for increased ocular complications in this age group due to poor compliance [9]. There is need for targeted contact lens education either in form of booklet or media campaign to encourage proper lens hygiene and improve compliance [20].…”
Section: Discussionmentioning
confidence: 99%